The Effectiveness of Elsa Speak Application in Teaching English Pronunciation - Dwi Saputra, Bunaken; Harmilawati; Sabaruddin (Universitas Islam Ahmad Dahlan (UIAD), 2025)
The findings of this study indicate that the ELSA Speak application is effective in improving the pronunciation ability of eighth-grade students at SMPN 7 Sinjai. This is evidenced by the results of the paired-sample t-test, which show a significance level of 0.000, lower than the significance threshold of 0.05; therefore, the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted. Accordingly, it can be concluded that the use of the ELSA Speak application has a significant positive effect on students’ pronunciation improvement. Furthermore, the N-Gain analysis reveals a score of 0.72 or 72%, which falls into the high effectiveness category. Descriptive statistical analysis also demonstrates an increase in students’ mean scores from the pretest to the posttest, indicating a significant improvement in students’ pronunciation performance after using the application. These findings are further supported by students’ positive responses during the learning process, in which they showed high levels of engagement, enthusiasm, and confidence in pronouncing English words. The ELSA Speak application also facilitates autonomous learning by providing immediate feedback, making pronunciation practice more effective, focused, and sustainable.